Semiotic analysis of Royco's flavoring advertisements on television - Ajeng Dinar Wisesa Wardhani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
An advertisement constitutes one of the important efforts for producers to open anyrelation to their consumers. It is known as one of the great way increasingly their trading. All ofthose things, by using advertisements those commercial goods can be known and be sold.Televisionis one of their choices to market their product. This research is talking about advertisement, by usingRoland Barthes Semiotic theories, combining Seassurian Structuralism theory. Actually, Seassuretheory consider as the basic of Barthes’ theories. Basically, Semiotic is a theory to show how ismeaning created and communicated in messages that are primarily visual. Semiotic approachanalyse the sign, icon, and symbol in television advertisements to intrepreting its meaning. Theproduction of meaning from visual messages, like advertisment has not been clearly investigated todesigners of advertising messages. The difficulty of taking visual meaning is the main reason ofstructured research approaches to code and categorize such information.